Synthesis and characterization of poly(N-methylpyrrole)/TiO2 composites on steel - Mahmoudian, M.R.; Alias, Y.; Basirun, Wan Jefrey (Elsevier, 2011)
Poly(N-methyl pyrrole) coating was successfully electrodeposited on steel substrates in mixed electrolytes of dodecyl benzene sulphonic acid (DBSA) with oxalic acid in the absence and the presence of TiO2 nanoparticles (NPs). The morphology and compositions were characterized by Field Emission Scanning Electron Microscopy (FESEM), Fourier Transform Infrared Spectroscopy (FTIR), Energy-Dispersive X-ray spectroscopy (EDX). X-ray Diffraction (XRD) and Transmission Electron Microscopy (TEM) were used to calculate the size of nanoparticles. Electrode/polymer/electrolyte system was studied by Electrochemical Impedance Spectroscopy (EIS). The FESEM micrographs suggest that the incorporation of TiO2 nanoparticles affects the morphology of the film significantly and makes the TiO2 to be loosely piled up with PMPy. The results of EIS showed that synthesized PMPy in the presence of TiO2 NPs increases and decreases the R-po and C-c of the coating respectively. The increase of the area of synthesized PMPy in the presence of nanoparticles can increase its ability to interact with the ions liberated during the corrosion reaction of steel in NaCl solution. (C) 2010 Elsevier B.V. All rights reserved.